Williams syndrome hypersociability: a neuropsychological study of the amygdala and prefrontal cortex hypotheses - Capitão, Liliana (2011)
Individuals with Williams syndrome display indiscriminate approach towards strangers. Neuroimaging studies conducted so far have linked this social profile to structural and/or functional abnormalities in WS amygdala and prefrontal cortex. In this study, the neuropsychological hypotheses of amygdala and prefrontal cortex involvement in WS hypersociability was explored using three behavioral tasks – facial emotional recognition task, a social approach task and a go no/go task. Thus, a group 15 individuals with Williams syndrome was compared to two groups of normal developing individuals – a group of 15 individuals matched for chronological age (CA) and 15 individualsmatched for mental age (MA), and sex. Individuals with WS present a specific impairment in recognizing negative facial expressions and do not display impairments in response inhibition when compared with typically developing groups. Although these findings partially support the amygdala contribution to WS hypersociability, we found that general cognitive functioning predicted this performance. Additionally, individuals with WS did not differ from both CA and MA groups in the recognition of angry facial expressions, a finding suggesting that they are actually able to identify stimuli associated with social threat. Overall, the results seem to indicate that this social profile must be understood within a developmental framework.